Clinico- haematological and biochemical features of natural Babesiosis in Nigerian breeds of Cattle (2018)
This study evaluated the haematological and biochemical changes associated with bovine Babesiosis. A total of 50 samples confirmed positive for Babesia spp from305 sera collected from clinically suspected cases of Babesiosis within a period of 9 months from some cattle farms in Oyo state, southwest Nigeria. Breeds were established by their morphological features, Age was estimated using rostral dentition and sexes morphologically determined. Haematological and Biochemical analysis were established by adopting standard procedures and the use of specific kits respectively. Results showed 32 (64%) was White Fulani breed, 8 (16%) was Sokoto Gudali breed, 8 (16%) was Red Bororo breed and 2 (4%) was Kuri breed. Female with 43 (86%), while the male had 7 (14%) susceptibility. Older cattle (≥4yrs) with 27 (54%) susceptibility, (3-3½yrs) with 17 (34%) susceptibility, while (2-2½yrs) had the least susceptibility of 6 (12%). Hematological analysis revealed best parameters in White Fulani breed with Mean ± SD of PCV 28.6 ±8.76, HB 9.3±2.98, RBC 7.5±2.44, while the least values were seen in Sokoto gudali breed with then following parameters; PCV 24.6±6.89, HB 8.1±2.29, RBC7.8±1.59. Biochemical analysis revealed White Fulani with the best values as follows; Total protein 5.5±1.87, Albumin 1.3±0.20, Globulin 4.2±1.73, Glucose 58.1±18.0, AST 60.3±15.68, ALT 50.7±14.80. For age group, the best parameters were observed in (3-3½yrs) group with the following; PCV 29.2±7.76, HB 9.4±2.72, RBC 7.6±2.52, Total protein 5.5±2.11, Glucose 56.9±20.31, AST 61.1±17.15 compared to age group 2-2½yrs with the following values; PCV 26.6±9.81, HB 8.3±3.28, RBC 7.1±2.27, Total protein 4.5±1.64, Glucose 49.3±20.85, AST 54±11.01. No significance difference in their indices except in blood urea nitrogen value which was significant among the breeds sampled. This investigation reveals variation in the susceptibility to natural Babesiosis among Nigerian cattle breeds, ages and sexes with generalise anaemia, lymphocytopaenia, neutrophilia, hypoproteineimia, hypoalbuminaemia and extremely low blood urea nitrogen.